Segmental Lung Lavage with Fiberoptic Bronchoscopy in a Patient with Special Presentation of Pulmonary Alveolar Proteinosis - Sadeghi, Hasan Allah (National Research Institute of Tuberculosis and Lung Disease, 2013)
Pulmonary alveolar proteinosis (PAP) is rare. It is characterized by the accumulation of proteinaceous materials in the alveoli. Typical appearance of BAL fluid (BALF) and positive PAS staining of BALF in conjunction with typical clinical and radiographic manifestations may be diagnostic of PAP. The current mainstay of treatment for PAP is whole-lung lavage. Therapy with granulocyte-macrophage colony stimulating factor is also an option. An alternative procedure is selective lobar/segmental lavage by fiberoptic bronchoscopy (FOB). Whole lung lavage with FOB for idiopathic PAP is currently a safe procedure in an experienced setting, and could be considered in patients with less severe lung involvement who cannot tolerate general anesthesia for the whole lung lavage. It provides long-lasting benefits. We report here our experiences with segmental lung lavage by FOB in a patient with vary severe PAP since she could not undergo whole long lavage under general anesthesia. The one year follow up results are also reported.